2018
DOI: 10.1177/1938640018762556
|View full text |Cite
|
Sign up to set email alerts
|

Calcaneal Osteotomy Safe Zone to Prevent Neurological Damage: Fact or Fiction?

Abstract: Level III: Retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…12 Respecting the anatomic landmarks, injury of the sural, medial plantar, and lateral plantar nerves was avoided. 12 In contrast, Wills et al found no significant difference in nerve injury between osteotomies performed inside or outside the “safe zone.” 18 However, in the present study, the injury rate of the sural nerve was significantly lower in the percutaneous group. The authors suggest that the “safe zone” only refers to the percutaneous technique of calcaneus osteotomy.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…12 Respecting the anatomic landmarks, injury of the sural, medial plantar, and lateral plantar nerves was avoided. 12 In contrast, Wills et al found no significant difference in nerve injury between osteotomies performed inside or outside the “safe zone.” 18 However, in the present study, the injury rate of the sural nerve was significantly lower in the percutaneous group. The authors suggest that the “safe zone” only refers to the percutaneous technique of calcaneus osteotomy.…”
Section: Discussioncontrasting
confidence: 67%
“…Wills et al presented results regardless of the osteotomy technique. 18 Wound healing problems after calcaneal osteotomy via the open approach are common, up to 28% in the literature. 1,6,7 In our study, 9 patients (15.5%) with open calcaneus osteotomy had wound healing problems and 6 (10.3%) of them had to be revised.…”
Section: Discussionmentioning
confidence: 99%
“…These authors concluded that the safety zone comprises the area formed on a lateral ankle x-ray by a line connecting the posterosuperior apex of the calcaneal tuberosity and the origin of the plantar fascia, and a line 11.2 mm anterior and parallel to it [7]. In contrast to that study, Wills et al found identical neurological injury rates between osteotomies performed inside and outside the "safety zone" [1]. As with Wills et al, we also found no significant difference between the occurrence of neurological injuries and the performance of the osteotomy inside or outside the "safety zone" (p = 0.163).…”
Section: Discussionmentioning
confidence: 94%
“…Calcaneal osteotomy is a procedure performed in routine clinical practice, its main objective is to re-establish the mechanical and load-bearing axis of the foot and ankle, demonstrating good and excellent results in the medium and long term [ 1 , 2 ]. Historically, potential complications associated with this surgery include surgical wound healing problems, infection, discomfort from the osteosynthesis material, over-/under-correction of the deformity, subtalar osteoarthritis, and iatrogenic fractures [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation